Impact of Service Recovery on Customer Loyalty: A Study of E-Banking in Spain - Frederic MARIMON; Luc Honore Petnji YAYA; Marti CASADESUS (Revista de Management Comparat International)
The purposes of this study are twofold: (i) to propose and apply a scale to measure service recovery in the electronic banking (e-banking) sector; and (ii) to examine the relationship between service recovery and customer loyalty in the setting of e-banking services. An online questionnaire is used to survey 123 Spanish customers of e-banking services using a modified version of the E-RecS-QUAL scale. The data are analysed by exploratory factor analysis to: (i) test the applicability of the scale to the setting of online bank services: and (ii) generate a model including constructs for e-recovery and e-loyalty. The study reassures online banks that a modified version of the E-RecS-QUAL scale is an appropriate instrument for measuring service recovery. The study also provides empirical evidence that responsiveness to requests and complaints has a positive influence on e-loyalty. The study is the first to provide definitive empirical evidence of the presumed link between the recovery dimensions proposed in the E-RecS-QUAL scale and the construct of e-loyalty.